Weaving the self and other: tracing the legacy of the Bauhaus - Leo, Jamie Jiaying (Nanyang Technological University, 2023)
In the early 20th century, the Bauhaus stood as one of the most influential art schools and institutions with German architect Walter Gropius at its helm. Asserting and advocating the radical concept of the material world reflecting the unity of all the arts, this approach was apparent through their craft-based curriculum and various workshops including ceramics, weaving, carpentry and more. Though born out of misogyny with most women being funnelled to the weaving workshop as a way of discouraging them from participating in other areas, the Bauhaus weaving workshop would go on to be one of the most productive workshops, training artists who would later go on to create and teach. My paper asserts that though the Bauhaus was operational for only a brief period of 13 years, the radicality embedded in the pedagogy of the Bauhaus weaving workshops was critical in enabling experiment within the fibre art realm today.